An Optimized Whole‐Mount Immunofluorescence Method for Shoot Apices. Issue 4 (7th April 2021) - Tran, Thu M.; Demesa‐Arevalo, Edgar; Kitagawa, Munenori; Garcia‐Aguilar, Marcelina; Grimanelli, Daniel; Jackson, David
Abstract: The localization of a protein provides important information about its biological functions. The visualization of proteins by immunofluorescence has become an essential approach in cell biology. Here, we describe an easy‐to‐follow immunofluorescence protocol to localize proteins in whole‐mount tissues of maize ( Zea mays ) and Arabidopsis. We present the whole‐mount immunofluorescence procedure using maize ear primordia and Arabidopsis inflorescence apices as examples, followed by tips and suggestions for each step. In addition, we provide a supporting protocol to describe the use of an ImageJ plug‐in to analyze colocalization. This protocol has been optimized to observe proteins in 2‐5 mm maize ear primordia or in developing Arabidopsis inflorescence apices; however, it can be used as a reference to perform whole‐mount immunofluorescence in other plant tissues and species. © 2021 Wiley Periodicals LLC. Basic Protocol : Whole‐mount immunofluorescence for maize and Arabidopsis shoot apices Support Protocol : Measure colocalization by JACoP plugin in ImageJ